1993
DOI: 10.1097/00003446-199308000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Evoked Potentials in Epileptic Patients

Abstract: Auditory brain stem response (ABR) and middle latency response (MLR] were recorded in 49 epileptic patients. Responses were evoked and recorded a t 90 dB nHL down to threshold. A statistically significant number of epileptic patients showed elevated ABR (30.l%] and MLR (40.7%) thresholds, even though their puretone audiograms showed normal hearing sensitivity. Threshold elevation was more frequent in subjects with grand ma1 epilepsy compared to s u b jects with temporal lobe epilepsy reflecting poorer response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…Such increases were also reported by Soliman et al, in a study involving epileptic patients 21. The authors found that middle latency responses (MLRs) and ASSRs were elevated in 40.7% of the epileptic patients.…”
Section: Discussionsupporting
confidence: 78%
“…Such increases were also reported by Soliman et al, in a study involving epileptic patients 21. The authors found that middle latency responses (MLRs) and ASSRs were elevated in 40.7% of the epileptic patients.…”
Section: Discussionsupporting
confidence: 78%
“…However, discrepancies between both measures have also been observed. Soliman et al (1993) report that approximately 30% of the epileptic patients in their study population showed elevated ABR thresholds although thresholds determined by pure tone audiometry (behavioral thresholds) were normal. In gerbils, ABR studies show that age dependent changes develop in animals older than 2 years (Boettcher et al, 1993; Mills et al, 1990).…”
Section: Discussionmentioning
confidence: 88%
“…These were predicted by Galambos 12 and confirmed by Worthington and Peters 13 and Kraus et al 14 and have since been seen by many other authors. [15][16][17][18] The ABR is not an objective hearing test in and of itself. Although synchronous responses following a normal latency-intensity function can be highly predictive of audiometric results, 19,20 an absent ABR need not mean absence of hearing sensitivity.…”
Section: The Continuummentioning
confidence: 99%